PENERAPAN STRATEGI PEMBELAJARAN PELATIHAN INDUSTRI (TRAINING WITHIN INDUSTRY) UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUKSI PADA SISWA KELAS IV SD NEGERI 81 PEKANBARU - Utama, Rahma Dwi; Antosa, Zariul; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis research was background by the low of student skill in creating construction things. This problem was caused by the teacher who did not give any opportunities to the student to develop their own idea, enough time, guidance to the student in creating their product and lack of evaluation toward students’ learning. This research was aimed to improve students’ skill in creating construction things at the 4th grades of SDN 81 Pekanbaru by applying training within industry learning strategy. The subject of the research was the 4th grades students with 31 numbers of students, while the object of the research was training within industry learning strategy to improve students’ skill in creating construction things.Based on the data analysis, the percentage of teacher’s activities was increased from cycle I to cycle II 30%, from 65% to 95%. The average percentage of students’ activities in cycle I was 60% with enough category and it was increased in cycle II to 85% with very good category. The total increase of students’ activities was 25%. From the result of teacher and students’ activities showed a progress. From the result of evaluation of creating construction things showed that the average initial score was 51.93, and it was increased in cycle I to be 58,25. Then, it was increased again in cycle II to be 77.20. So, by implementing the training within industry learning strategy can improve the skill in creating construction things.Keywords : Training Within Industry, Creating Construction Things Skill.